2021
DOI: 10.1002/jrs.6128
|View full text |Cite
|
Sign up to set email alerts
|

Raman anisotropy in serpentine minerals, with a caveat on identification

Abstract: The serpentine minerals lizardite, polyhedral serpentine, chrysotile, antigorite and 15-sector and 30-sector polygonal serpentine have been studied by micro-Raman spectroscopy, using selected samples, that had been previously characterized. The appropriate crystal orientations were determined by optical microscopy of petrographic sections. Oriented spectra, obtained using Nd-YAG green laser radiation (532 nm), were deconvolved, extracting wavenumber and intensity values for the peaks, possibly overlapping and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…As far as phase identification is concerned, we make reference again to Compagnoni et al (2021). In the case of lighter domains, the two sharp peaks at 3686 and 3705 cm −1 well match the values of 3688 and 3706 cm −1 previously reported for the ω-ω section of lizardite.…”
Section: µ-Raman Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…As far as phase identification is concerned, we make reference again to Compagnoni et al (2021). In the case of lighter domains, the two sharp peaks at 3686 and 3705 cm −1 well match the values of 3688 and 3706 cm −1 previously reported for the ω-ω section of lizardite.…”
Section: µ-Raman Resultssupporting
confidence: 77%
“…1e, right), being the one with better phase resolution. Furthermore, as shown by Compagnoni et al (2021), this orientation does not present anisotropic Raman effects. Therefore, a simpler interpretation may be expected.…”
Section: µ-Raman Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Mellini and Viti (1994) and Viti and Mellini (1997) initially characterised samples of the Monte Fico lizardite vein by optical microscopy, X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. Since then, the sample has been studied using a diverse range of approaches, including neutron diffraction (Gregorkiewitz et al, 1996), thermal analysis (Viti, 2010), Mössbauer and infrared spectroscopy (Fuchs et al, 1998;Trittschack et al, 2012), Raman spectroscopy (Rinaudo et al, 2003;Auzende et al, 2004;Trittschack et al, 2012;Capitani et al, 2021;Compagnoni et al, 2021), X-ray diffraction (Hilairet et al, 2006), and calorimetry (Gailhanou et al, 2018). Additionally, Monte Fico lizardite has been used as a starting material for several rock deformation experiments (Hirose et al, 2006;Viti andHirose, 2010, 2009;Amiguet et al, 2014;Tesei et al, 2018).…”
Section: Monte Fico Lizardite Veinmentioning
confidence: 99%
“…Recently, Compagnoni et al (2021) and Capitani et al (2021) reported a significant Raman anisotropy effect in the serpentine minerals lizardite and polyhedral serpentine, which results in wavenumber shifts depending on the orientation of the crystals relative to the impinging excitation laser. In particular, they noted a shift of more than 10 cm −1 in the position of the main band in the OH-stretching region for lizardite.…”
Section: Introductionmentioning
confidence: 99%